Variabel Ekonomi dan Stock Return - Teddy Jurnali; Riko Andriko (Global Financial Accounting Journal, 2017)
The purpose of this research aimed to analyze the effect of Macro Economy variables: Gross Domestic Product (GDP) Growth, Inflation, Interest Rate, Exchange Rate, and Money Supply and Micro Economy variables: Profitability, Leverage, Market Value, Earning Management, and Firm Size on Stock Return for all listed firms in Indonesian Stock Exchange during the period 2009-2013. The sample of this research were selected using the purposive sampling method and 357 firms or 1.785 observations data used in this research. It used panel regression method to analyze data with Eviews version 7st (Eviews 7). The results of this research shows that all Macro Economy variables and Profitability, Leverage, Market Value (Dividend Yield), and Earning Management are the variables that have significant effect to Stock Return. However this research found that Market Value (Book to Market Ratio), and Firm Size are insignificant to Stock Return in Indonesia Stock Exchange.